?Carrot and Citrus Juice Waste as Potential Source of Dietary Fiber (Biological Sciences - PJSIR, 1995)
There is a growing community awareness of the impor-. tance of an adequate intake of dietary fibers. There is a potentialfor many fruits, vegetables and cereal residues as dietarysupplements and in food manufacture.